Electrical effects of GNP/Ag/SA conductive epoxy on copper flexible substrate - Hussin, Hazril Hisham (2024)
Various efforts to improve the performance of printed conductive ink have been conducted in order to obtain its full performance potential. This includes the investigation on the effect of conductive filler particle size towards the electrical conductivity performance. This study focuses on the product condition and electrical performance of graphene nanoplatelet (GNP), silved nano particle (Ag) and silver acetate (SA) as hybrid conductive filler components by varying the particle size of only one the filler component, which is GNP. The GNP/Ag/SA formulation with organic solvent was used by preparing three samples utilizing different GNP particle sizes of 5 µm and 25 µm. The purpose of this experiment is to collect data on the electrical conductivity of ink when employed in circuits and determine the best formulation of conductive ink. The obtained results revealed differences between the inks produced using 5 µm and 25 µm of GNP sizes. The resistivity of the 5 µm samples were was lower than 25 µm samples. The GNP of 5 µm recorded the lowest resistivity of 2.48 x 10-5 Ω.m as compared to 2.63 x 10-5 Ω.m recorded by 25 µm samples. The lower resistivity value indicates that the conductive ink formulated using 5 µm of GNP size has better electrical conductivity performance. The results signify that by using different particle sizes of only one component of hybrid conductive fillers produced different conductive ink performance, especially the electrical conductivity.